Abdominal cocoon syndrome (idiopathic sclerosing encapsulating peritonitis): An extremely rare cause of small bowel obstruction—Two case reports and a review of literature - Alsadery, Humood A.; Busbait, Saleh; AlBlowi, Abdulrahman; Alsawidan, Morshed; AlBisher, Hassan Mohammed; Alshammary, Shadi (Frontiers in Medicine, 2022)
Abstract: Introduction Sclerosing encapsulating peritonitis (SEP) is a rare cause of intestinal obstruction in which the bowel and internal abdominal organs are wrapped with a fibrocollagenous cocoonlike encapsulating membrane.1,2 SEP divided into two entity Abdominal cocoon (AC) also known as idiopathic or primary sclerosing encapsulating peritonitis which is extremely rare type and secondary Sclerosing encapsulating peritonitis more common type. Case presentation Two male patient from India , a 26- and 36-year-old presented to our hospital compiling of abdominal pain associated with nausea and vomiting without history of previous surgical intervention patient vitals were stable. Preoperative diagnosis of abdominal cocoon were establish by abdominal Computed tomography. It showed Multiple dilated fluid filled small bowel loops in the center of the abdominal cavity with thin, soft tissue non-enhancing capsule encasing the small bowel loops with mesenteric congestion involving small and large bowel loops. Both patient underwent complete surgical excision of sac without intraoperative complication. patients had smooth postoperative hospital course and were discharge home in good condition. Conclusion Patient with abdominal cocoon have nonspecific clinical presentation of intestinal obstruction. High index of clinical suspicion in combination with appropriate radiological investigation will increase the chance of preoperative detection of abdominal cocoon. In patient with complete bowel obstruction complete excision of the peritoneal sac is the stander of care.